THE ROLE OF ACADEMIC ADVISORS IN IMPROVING MEDICAL STUDENTS’ MOTIVATION: A CASE-STUDY - Ita Armyanti (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2020)
Introduction: Providing assistance and student support, especially in medical education, play pivotal role in medical students education. The role of academic advisor, would run properly, if it has the ability as a counselor. This article aims to describe the role of academic advisors in improving the learning motivaton in medical students, using case presentation approach.Discussion: The role of academic advisors as a counselor, would occur if it has ability as counselor, ability to empathize, effective communication skill, and tailored to students characteristics. Increasing students’ motivation, could be done through the utilization of the third environment. The family bonding plays an important role to imporve students’ learning motivation.Conclusion: Providing assistance and student support should be given according to students’ problems and characteristics. The role of an academic advisors, as a counselor, would improve students’ motivation to learn.